THE INCIDENCE AND ASSOCIATED RISK FACTORS AFFECTING THE RATE OF ECTOPIC PREGNANCY IN PRIME AND MULTIGRAVIDA WOMEN IN SULAIMANI MATERNITY TEACHING HOSPITAL - Fattah, Chro; Moheeddin, Huda; Hawrammi, Fattah (Journal of Sulaimani Medical College, 2017)
Background Ectopic pregnancy (EP) is a potentially life-threatening condition and still the major cause of maternal mortality in the first trimester of pregnancy. It accounts for approximately 10% of maternal deaths. Despite major advances, early diagnosis of EP is still a challenge for clinicians. In the past 20 years, the use of sensitive βhCG tests, high-resolution transvaginal ultrasound, and advances in laparoscopy (LS) have enabled the detection of EP without tubal rupture. Objectives The aim of the study is to determine the incidence and associated risk factors for ectopic pregnancy, and to address these risk factors in prime gravid and multigravida. Patients and Methods This study was conducted in the period from January the 1st 2015 to the July 1st 2015, all ectopic pregnancy patients admitted to Sulaimani Maternity Hospital were collected. Data from 100 patients recorded, however we didn’t have all variables from 7 patients, we analyzed 93 of the cases. Written consent for the study was obtained from all the patients. Results Our results show weight and BMI were demographic changes that most significantly affect the results. The higher the weight the higher the risk of ectopic pregnancy. Only (11.8%) has no risk factors, most of patient had multiple risk factors (63.4%) were among multiparas women and (24.7%) had only one risk factors. Conclusion We found the main demographic variable was High body weight and BMI. Most of the patient have multiple risk factors and risks higher in multigravida women than prime gravid. The most significant risk factor for increasing the rate was confirmed with previous ectopic pregnancy, combined contraception pills. Pathological vaginal discharge, and previous caesarean section. We found this increase may be due to poor in c/s technique and increase in the rate of caesarean section on request especially in private sector. This study is was unique in the area to address these risk factors for ectopic pregnancy.
Keywords: Ectopic pregnancy; Risk factors; Previous ectopic pregnancy; Vaginal discharge